Pendampingan Desain Kemasan Produk Kacang Tanah Barandang untuk UMKM di Nagari Tigo Balai - Delvi Yanti; Aninda Tifani Puari; Fadli Irsyad; Eri Stiyanto (Warta Pengabdian Andalas, 2024)
When comparing Lawang to Nagari Tigo Balai, the latter exhibits an attractive appearance on product packaging, which is one of the crucial factors in the marketing strategy of micro, small, and medium enterprises (UMKM). UMKM's issues in the Nagari Tigo Balai area include limited technology and knowledge in redesigning packaging. This Community Service Activity (PKM) aims to assist UMKM in Nagari Tigo Balai in designing packaging for "Barandang" peanut products. The method consists of three stages: observation, analysis of the content of "Barandang" peanut products, and assistance in designing packaging until the design is ready for printing. The result of the assistance activity is the creation of packaging designs for "Barandang" peanut products for two UMKMs in Nagari Tigo Balai, namely LBM and ARYA, with nutritional information on the packaging. Based on the discussion during the assistance activity, this packaging redesign assistance plays a crucial role for UMKM practitioners in making their marketed products more attractive, thus increasing buyers' interest and purchasing power even further.